Financing College Education in the Private Sector in Kerala - E T Mathew (Economic and Political Weekly April 28, 1990, 1990)
This study attempts an evaluation of the various sources of funds, both public and private, for the financing of private colleges in Kerala and the changes in the pattern and trends of financing over time. In the context of the generally held opinion that the phenomenal growth in the number of colleges during the last three decades has been accompanied by a qualitative deterioration in standards, the paper also discusses the relationship between the manner of financing and academic standards as judged by the professional qualifications of the teaching staff and examination results